2017
DOI: 10.1136/bcr-2017-221842
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland: an unusual site of breast cancer metastasis

Abstract: Parotid gland metastases from breast cancer are an extremely rare and unusual event with a limited number of cases recorded in the literature. A 71-year-old woman with a history of ductal adenocarcinoma of the left breast presented to the maxillofacial clinic with an asymptomatic swelling of the left parotid gland. The presentation occurred 21 years after she underwent treatment for recurrent breast cancer. Investigations led to the diagnosis of a breast cancer metastasis which was oestrogen receptor and proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“… 24 , 27 The same decision is applicable to parotid metastasis of breast cancer, but attention should be paid to the protection of the facial nerve during operation. 28 , 29 For digestive system metastasis, some researchers advocated that systemic treatment should be used as a first-line clinical decision 30 and surgical resection should be applicated only when presenting with obstruction symptoms. 31 But compared with the first-line application of systemic therapy combined with local resection, the improvement of median survival time of patients is still controversial, and there is no significant difference in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive management differs significantly however, with nasopharyngeal malignancies being more amenable to primary chemoradiotherapy, while our case was definitively treated with combined surgical and oncological treatment modalities. In addition to the nasal septum, there are numerous reports of parotid metastases arising from more unusual sites including kidney, liver, lung and breast 18–21. As a result, otolaryngology and oncology teams alike should be mindful of rarer primary sites in cases of unusual parotid tumours.…”
Section: Discussionmentioning
confidence: 99%